INTRICACIES OF DECODING STUDENT PERFORMANCE - Him, Celbert M.; Himang, Melanie M. (Journal of Agriculture and Technology Management, 2012)
The  purpose  of  this  research  was  to  determine the  extent  of  practices on  the  details  of  d ecoding performances of students done by selected faculty members of the Cebu Technological University using a descriptive method of research.  It was found out that both the students and the faculty members believed that the different means of informing students, process of recording, grade computation and grade transparency and feedback  system  were  practiced. Still  this  finding  implies  the  need  for  improving the  activities of  decoding performance of students to be very evidently done as grade is the basic currency of educational system. Moreover, faculty members and students have a positive attitude towards the importance of doing the aforementioned tasks of decoding performance of students. Students attitude toward these tasks suggest the need for uniformity of decoding process as well as transparency of its results with less apprehension for any possible feedback about the coded performance.